Improvement of fire protection of fabrics with intumescent coatings - Tsapko, Yu.; Sukhanevich, M.; Bondarenko, O.; Tsapko, O. (Ways to Improve Construction Efficiency, 2022)
Based on the analysis of literature sources, the article finds that today it is difficult to imagine the protection of human lives from fire without fire-retardant coatings on textiles. Precisely defined standards allow to determine the requirements for textile materials that have fire protection. It is hardly possible to prevent the inflammation of textiles due to their physical parameters (melting point, flash point). However, it is possible to extend the time for people to escape to start rescue operations by using appropriate fire protection systems or a combination of individual active ingredients. Reducing flammability and developing flammable and combustible materials is one of the main ways to prevent fires and solve the problem of expanding the scope of these materials. Treatment with flame retardants significantly affects the spread of flames, can significantly reduce the ability to smoke and heat. Therefore, research aimed at determining the patterns of fire protection paths used for the manufacture of textiles is relevant. One of such promising areas is the study of the formation of a layer of foam cone in the fire protection of the fabric with intumescent coatings. Experimental studies to determine the fire-hazardous properties of the tectile material revealed the ignition of the untreated sample, while for the fire-retardant – the process of ignition and spread of the flame did not occur. Inhibition of the process of ignition and spread of flame for such a sample is associated with the decomposition of flame retardants under the action of temperature with heat absorption and release of non-combustible gases (nitrogen, carbon dioxide), changing the direction of decomposition towards non-combustible gases and flame retardant coke. This indicates the possibility of transition of the textile material during the processing of the composition to materials that are flammable, do not spread the flame on the surface.